Where shall I wander new poems - Ashbery, John 1927-2017 (Ecco, 2005)
You meant more than life to me. I lived through you not knowing, not knowing I was living. I learned that you called for me. I came to where you were living, up a stair. There was no one there. No one to appreciate me. The legality of it upset a chair. Many times to celebrate we were called together and where we had been there was nothing there, nothing that is anywhere. We passed obliquely, leaving no stare. When the sun was done muttering, in an optimistic way, it was time to leave that there.
Keywords: American poetry -- 21st century